2015
DOI: 10.1016/j.ccell.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

ERK2-Dependent Phosphorylation of CSN6 Is Critical in Colorectal Cancer Development

Abstract: SUMMARY Biomarkers for predicting prognosis are critical to treating colorectal cancer (CRC) patients. We found that CSN6, a subunit of COP9 signalosome, is overexpressed in CRC samples and that CSN6 overexpression is correlated with poor patient survival. Mechanistic studies revealed that CSN6 is deregulated by EGFR signaling, in which ERK2 binds directly to CSN6 Leu163/Val165 and phosphorylates CSN6 at Ser148. Furthermore, CSN6 regulated β-Trcp and stabilizes β-catenin expression by blocking the ubiquitin-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 55 publications
4
89
0
Order By: Relevance
“…For instance, deubiquitination of HSP70 and Snail by CSN5 were reported to modulate exosomal protein sorting (Liu et al, 2009) and to enhance cancer cell invasion and migration (Wu et al, 2009), respectively. Recently, phosphorylation of CSN6 by ERK was found to stabilize β-catenin for colon cancer cell proliferation (Fang et al, 2015). These results demonstrated that the deubiquitination activity of the CSN family is crucial for cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, deubiquitination of HSP70 and Snail by CSN5 were reported to modulate exosomal protein sorting (Liu et al, 2009) and to enhance cancer cell invasion and migration (Wu et al, 2009), respectively. Recently, phosphorylation of CSN6 by ERK was found to stabilize β-catenin for colon cancer cell proliferation (Fang et al, 2015). These results demonstrated that the deubiquitination activity of the CSN family is crucial for cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…CSN6 contributed to Myc stability through the CSN‐Cullin‐Fbxw7 axis during tumorigenesis in breast and pancreatic cancers 24 . CSN6 could also regulate β‐catenin stability by regulating ubiquitination in colorectal cancer 25 . EGFR‐ERK‐related pathways have been shown to regulate CSN6 expression to stabilize β‐catenin 25 .…”
Section: Introductionmentioning
confidence: 99%
“…CSN6 could also regulate β‐catenin stability by regulating ubiquitination in colorectal cancer 25 . EGFR‐ERK‐related pathways have been shown to regulate CSN6 expression to stabilize β‐catenin 25 . In addition, EGF could upregulate the expression of B3GNT3 to enhance the stability of PD‐L1 protein in triple‐negative breast cancer 26 .…”
Section: Introductionmentioning
confidence: 99%
“…CSN6 reportedly controls the proliferation and metastasis of glioblastoma by chromatin immunoprecipitation-mediated degradation of epidermal growth factor receptor (EGFR) [15], extracellular regulated protein kinases (Erk)1/2-dependent phosphorylation of CSN6 is critical in colorectal cancer development [16]. We examined whether CSN6 is involved in Fig.…”
Section: Csn6 Knockdown Down-regulate Phosphorylation Signaling Pathwaymentioning
confidence: 99%